Advancing Renewable Energy: An Experimental Study of a Switched-Inductor, Switched-Capacitor Luo Boost Converter for Low-Voltage Applications - Ertekin, Davut; Baltaci, Kuebra; Celebi, Mehmet; Alepuz, Salvador (Mdpi, 2023)
Photovoltaic (PV), battery, and fuel cell (FC) technologies are emerging forms of renewable energy gaining popularity. However, one of the key limitations is their production of direct current (DC) voltage, which hinders the connectivity and integration with the electrical grid. To address this issue, various DC/DC boost converters have been introduced. This study presents an innovative Luo converter with a switched-inductor-capacitor (SLC) cell at the input and a switched-capacitor (SC) cell at the output. The SLC cell not only increases the input voltage, but also enhances the source's lifespan and reliability. The SC cell further amplifies the voltage, especially for high-gain applications. The proposed converter simplifies control processes by using a single power switch, significantly boosting the input voltage by 21 times with a duty ratio of 0.8. This surpasses the gains achieved by conventional boost converters by over fourfold and Luo converters by sevenfold. The second challenge when a converter is connected to these voltage sources is the potential reduction in the lifespan of the sources and the overall system due to large input current ripples. The proposed converter addresses this issue by incorporating a switched-capacitor cell on the input side. This cell charges the inductors in parallel and discharges them in series, reducing the magnitude of the input current. Another advantage of the proposed converter is its simplicity, as it employs only one power switch, minimizing the complexity of the controller system. Additionally, the distribution of the output voltage passing through the diodes between the switch and output capacitor helps mitigate voltage stress for all semiconductor devices and capacitors. The study includes thorough mathematical analyses, simulations, and laboratory tests to validate the research's theoretical foundations.
Keywords: Luo converter; switched-inductor cell; switched-capacitor cell; DC/DC boost converter; renewable energy sources